UPAYA MENCETAK CALON GURU PROFESIONAL DI PESANTREN (Studi Kasus di Pondok Pesantren Al-Iman Ngambakan Ponorogo Jawa Timur) - Muhammad Muflih; Islam, Saiful (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2023)
The aim of the class VI KMI program is to shape humans into a group of leaders and provide benefits to the universe which in the end is expected to be a role model for all mankind. The purpose of the process of implementing the class VI KMI program is to produce professional Al-Iman Babadan Islamic Boarding School teachers for all class VI students as a prerequisite for further graduation. The